Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine

H5IO6, as an efficient reagent for the aromatization of tetrahydro-β-carbolines: total synthesis of norharman, harmane, harmine, kumujian-C, and orthoscuticellines B - Sabane, Jagjivan K.; Gaikwad, Sunil V.; Gajbhiye, Jayant M.; Kumar, Pradeep (ChemistrySelect, 2026)
A new method is reported for the synthesis of beta-carbolines and their derivatives using H5IO6 in DMSO solvent. The method is mild and efficient for oxidative decarboxylation and aromatization of tetrahydro beta-carbolines (TH beta C), resulting in good to excellent yields (70% to 88%) of beta-carbolines. This protocol has further been utilized for the synthesis of beta-carbolines based natural products, for examples, norharmane, harmane, harmine, Kumujian-C, and Orthoscuticellines A and B.
Keywords: aromatization; beta-carboline; H5IO6; Harmine; orthoscuticellines; Oxidative